Ramrod penis with unilateral inguinal bubo - Yogindher Singh (Wolters Kluwer Medknow Publications, 2024)
Lymphogranuloma venereum (LGV) is a sexually transmitted disease caused by Chlamydia trachomatis. Classically, LGV is characterized by the development of a transient genital ulcer or papule, followed by the appearance of tender femoral and/or inguinal lymphadenopathy. Esthiomene, a rare late manifestation of, LGV is a primary infection affecting the lymphatics of the penis, scrotum, or vulva. The male genitalia are affected less commonly by esthiomene. Here, we report a male patient who presented with a Ramrod penis along with an enlargement of inguinal lymph nodes.